Penerapan Strategi Pembelajaran Berbasis Pengalaman Dalam Menginternalisasikan Nilai Keimanan Kepada Allah SWT di SMA Muhammadiyah 5 Lubuk Pakam - Widya Syahrani Jambak; Nikmah Royani Harahap; Umy Fitriani Nasution (Fakultas Agama Islam Universitas Al Washliyah, 2025)
Globalization and the advancement of information technology impact students' mindsets and behavior, often leading to a lack of religious awareness and morality, posing a challenge in education. Although experience-based learning is effective in religious education, its implementation at SMA Muhammadiyah 5 Lubuk Pakam has not been thoroughly explored. This study aims to investigate the process of internalizing faith values in students and the strategies used by teachers to connect students with religious teachings through real-life experiences. Employing a qualitative case study approach, data were collected through in-depth interviews, participant observations, and document analysis from two Islamic Religious Education teachers, six 11th-grade students, the vice-principal, and the principal. Data were analyzed using an interactive model, triangulation, and member checking. The findings indicate that the implementation of experience-based learning strategies successfully internalized the values of Sincerity (Ikhlas), Shame (Malu), and Asceticism (Zuhud) through reflective discussions, storytelling, and brainstorming. Students showed positive responses, with improved understanding and behavioral changes for the better. This success is supported by the teachers' roles and student enthusiasm, despite challenges such as limited time and variations in students' openness to sharing spiritual experiences. This strategy not only enriches students' cognitive knowledge but also strengthens their commitment to practicing religious values in daily life.